Idiosyncratic Risk and Higher-Order Cumulants - Frederik Lundtofte; Anders Wilhelmsson (Lund University, School of Economics and Management, Department of Economics, 2011)
We show that, when allowing for general distributions of dividend growth in a Lucas economy with multiple "trees," idiosyncratic volatility will affect expected returns in ways that are not captured by the log linear approximation. We derive an exact expression for the risk premia for general distributions. Assuming growth rates are Normal Inverse Gaussian (NIG) and fitting the distribution to the data used in Mehra and Prescott (1985), the coefficient of relative risk aversion required to match the equity premium is more than halved compared to the finding in their article.
Keywords: C13; G12; 330; diosyncratic risk; idiosyncratic volatility; risk premia; cumulants; NIG distribution